The design of a readily attachable and cleavable molecular scaffold for ortho-selective C–H alkenylation of arene alcohols. Issue 3 (18th December 2015) - Knight, Brian J.; Rothbaum, Jacob O.; Ferreira, Eric M.
Abstract : A novel molecular scaffold with distinct features (easily attachable, removable, recoverable) induces Pd-catalyzed oxidative olefinations when attached to arene alcohols. Abstract : We describe herein the design of a novel molecular scaffold that can induce facile oxidative olefinations when attached to alcohols. Benzylic, homo-, and bishomobenzylic alcohols are utilized. The scaffold can act as a protecting group for the alcohol in other transformations, and it is recoverable in excellent yield. The overall sequence can also be telescoped without purifications of intermediates, representing a net alcohol-based directed ortho -alkenylation.